Evidence of time‐dependent prognostic factors predicting early death but not long‐term outcome in primary CNS lymphoma: a study of 91 patients1. Issue 2 (9th August 2012) - Ghesquières, Hervé; Drouet, Youenn; Sunyach, Marie Pierre; Sebban, Catherine; Chassagne‐Clement, Catherine; Jouanneau, Emmanuel; Honnorat, Jérome; Biron, Pierre; Blay, Jean Yves
Abstract Long‐term primary CNS lymphoma (PCNSL) survivors could have multiple adverse prognostic factors at diagnosis such as age, performance status (PS), site of the tumour (deep vs superficial), lactate dehydrogenase (LDH) level and CSF protein level. Whether these five prognostic factors integrated in the International Extranodal Lymphoma Study Group (IELSG) score have a time‐dependent effect is questionable. Among 132 PCNSL patients treated at our institution between 1984 and 2006, 91 available patients for IELSG score were evaluated by time‐segmented analysis. Of the 91 patients, 21% had 0–1, 59% had 2–3 and 20% had 4–5 adverse IELSG prognostic scores. With a median follow‐up of 102 months, the median overall survival (OS) of the 91 patients with the five prognostic factors of IELSG score was 33 months (95% CI, 17 to 55) compared with 14 months (95% CI, 3 to 23) for the remaining 41 patients whose CSF protein level was lacking in the IELSG score. These 41 patients who did not have lumbar puncture presented a poorer PS at diagnosis and a lower treatment response rate. While confirming the prognostic value of the IELSG score, we observed a time‐dependent effect of age, PS and tumour site; all three lost their prognostic value after 6 months from diagnosis, while LDH remained a constant predictor of OS. No prognostic impact of CSF protein level was reported. Patients with older age, poor PS and deep brain involvement are at risk of death during the first months after diagnosis but could have a favourable long‐term outcome after the treatment period. New prognostic factors predicting long‐term outcome remain to be determined. Copyright © 2012 John Wiley & Sons, Ltd.